Evaluasi Kebijakan Pencegahan Stunting di Kabupaten Asmat Provinsi Papua Selatan - Rerey, Heni Voni; Masrif, Masrif; Mogan, Martina; Wahyuni, Sri (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Background: The prevalence rate of stunting in the last 2 years in Papua Province from 29 regencies/cities with the highest stunting cases, namely Asmat Regency, has increased, namely in 2021 by 38.1%, rising to 54.5% in 2022. Objective: To evaluate prevention policies Stunting in ASMAT Regency, South Papua Province. The research method is qualitative descriptive by conducting in-depth interviews, Focus Group Discussions (FGD) and observation. The selection of informants in this research used a purposive sampling technique. There were 12 informants in the research. Research instruments: interview guide, in-depth interview recording tool. Data Analysis Using Content Analysis. Research results: The obstacles to implementing stunting prevention policies from the input side are that human resources are still lacking and community health centers which are far from the Health Service cannot implement the 1000 HPK program. The obstacles to the process component are the cadres who cook the food for 1000 HPK (not nutrition officers) so it is found that there are still vegetables that are too cooked in cooking and the lack of counseling from Health Officers when monitoring meals on the spot at the 1000 HPK Post, recording and reporting from the midwife guarding the 1000 HPK Post less complete. Obstacles from the Output Component of basic immunization coverage are still some that have not met the target because parents are prohibited from immunizing and when the baby is re-visited for immunization, the baby has been taken to the forest to look for food for months or even years, carrying pregnant women and children. child. Suggestion: it is best to issue a policy from the Regent to prohibit pregnant women and children from being taken into the forest to look for food so that they can participate in the 1000 HPK program from the beginning of pregnancy until the baby is 2 years old to prevent stunting.